The resources crisis - Louis W. Stern; Tayeb Zahzah (Intereconomics, 1975)
This article utilizes a new concept of supply and demand for raw materials. It emphasizes the need for the use of long run economics rather than short run analysis in the determination of a fair price for raw commodities.
Keywords: 330; Raw Materials